Os significados e sentidos atribuídos ao papel do psicólogo escolar, por parte daqueles que atuam na APAE: uma construção cercada de equívocos - Saquetto, Danielle Juvat (2008)
The aim of the present research is to identify the sense and significant attributed to the role of educational psychologists by those working at APAEs, institutions which offer educational services for people who carry mental or multiple deficiencies. The theory which oriented such study was the socio-historical one, followed by a qualitative research method. Two psychologists who work at one APAE located in a city of the state of São Paulo were invited to participate in the systematic investigation answering a questionnaire in order to identify their social, cultural and economical level, as well as an interview whose goal was to identify the sense and significant that they attributed to their professional activity. Also, both participants were observed during a one whole working day, in order to be better acquainted with the context they were to talk about. The results pointed out that the academic training received by psychologists who are willing to work in the educational field does not prepare them to deal with handicapped people. For this reason, their performance has been based mostly in their empirical experiences, without support of any theoretical thought. As a consequence, APAEs psychologists professional practices are full of mistakes and misconceptions, some of which lead them to believe that they have to exert a clinical role in educational institutions, to evaluate children, to label them and even to act as magicians, in transforming the children. In this context, many psychologists become vulnerable professionals, who end up adopting distorted roles and postures, often pathological and fragmented ones, which only lead to inefficiency and frustration, since they are in constant conflict with the desired professional performance, which can be highlighted as follow: a) to stimulate a critical mindset about APAEs reality, therefore to identify its restrictions and advantages; b) to see handicapped people as humans beings that are socio-culturally constructed, who deserve to have their pedagogical needs better fulfilled through an interdisciplinary and holistic perspective